I Am Just Beginning - Howey, Ella Mae (Tufts Archival Research Center, 2006)
Ella Mae Howey states her belief in a personal, loving God who provides abundant life opportunities, and describes how learning to manage her condition of hearing loss taught her to believe in her power to respond positively to life's challenges.